2009
DOI: 10.1111/j.1464-410x.2009.08539.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of significant risk factors affect perioperative outcomes after robot‐assisted radical cystectomy?

Abstract: OBJECTIVE To evaluate the effect of preoperative risk factors on perioperative outcomes up to 3 months after robot‐assisted radical cystectomy (RARC), as RC continues to be associated with a high rate of morbidity and mortality. PATIENTS AND METHODS From 2005 to 2007, 66 consecutive patients had RARC at Roswell Park Cancer Institute. Patient demographics, preoperative risk factors and complications up to 3 months after RARC were reviewed from a prospective quality‐assurance database. Patients were stratified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Complications associated with RARC and risk factors for complications have been discussed in case series. 19,26,[34][35][36][37][38][39] Johar et al analyzed the data obtained from the IRCC database of 939 patients treated with RARC. 40 The mean EBL was 580 mL; the mean hospital stay was 11 days; the admission rate within 30 or 90 days was 13% or 20%, respectively; and the mortality within 30 and 90 days was 1.3% and 4.2%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications associated with RARC and risk factors for complications have been discussed in case series. 19,26,[34][35][36][37][38][39] Johar et al analyzed the data obtained from the IRCC database of 939 patients treated with RARC. 40 The mean EBL was 580 mL; the mean hospital stay was 11 days; the admission rate within 30 or 90 days was 13% or 20%, respectively; and the mortality within 30 and 90 days was 1.3% and 4.2%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
“…Complications associated with RARC and risk factors for complications have been discussed in case series . Johar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Different parameters may affect outcome and risk for surgery-related complications such as age, higher ASA score or previous surgery. Butt et al did not find a significant association between age, BMI, ASA score and complication rate in their series of 66 RARC cases 44 .…”
Section: Surgery-related Complicationsmentioning
confidence: 80%
“…Stricture rates following robot-assisted radical cystectomy range from 1.5% to 17.6%, and are comparable to rates observed following open procedures, although studies have been limited by small patient numbers [40][41][42][43][44][45][46] . In their series of 468 patients at median follow-up of 8.2 months, Andersen et al found no significant difference in stricture rate between the open and robot-assisted groups 1 .…”
Section: Mode Of Surgerymentioning
confidence: 91%